Migraine Synonyms in South Indian coastal population- A retrospective study - Francis, M. V. (International Journal of Research in Medical Sciences, 2023)
Background: A direct question like, do you get headaches or had headaches in the past will not unravel past history of migraine in many patients in Southern coastal region of India. This study was conducted to document migraine synonyms in this population. Methods: A 5-year retrospective study was conducted in three outpatient clinics in a coastal region of Southern India. When children were brought with recurrent headaches, as an aid to diagnosing migraines, family history of headache or migraine was recorded from their mothers and grandmothers. They were asked two questions - 1) do you get headaches or 2) suffered from headaches in the past. If they replied in the negative, a third question was asked (Do you get any head discomfort /head pain along with any other illness). Results: Out of 7000 mothers and grandmothers interviewed, 1778 reported headache in the past resembling migraine or probable migraine. 1001 who said no headache in the past, were getting other migraine synonym disorders in which headache was one of the complaints. 22 different synonyms which fitted into migraine diagnostic features were documented in this group of study participants. Conclusions: To diagnose migraine and its subtypes, 2 (aura) to 5 (without aura) past episodes are mandatory. This study proves that a sound knowledge about local migraine synonyms and slangs are important to elicit past history of migraine. Headache epidemiological studies can be flawed if only one leading question like do you get headaches/suffered from headache in the past is asked.